Thermoluminescence studies of calcium metaborate (CaB2O4) nanocrystals synthesized by solution combustion method (Malaysian Journal of Fundamental and Applied Sciences, 2017)
This study reports the thermoluminescence properties of calcium metaborate (CaB2O4) nanocrystals prepared by solution combustion method. The characterization by X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM) and energy dispersive X-ray (EDX) analysis was presented here. The XRD patterns showed the orthorhombic structure with the crystallite size at about 27 nm and the FESEM micrograph revealed the formation of irregular spherical shape nanoparticles. Weight fraction obtained from EDX analysis consequently lead to determination of effective atomic number. It was found that the effective atomic number of CaB2O4, Zeff= 14.13 was equivalent to the effective atomic number of the bone, Zeff= 13.23 with percent error 6.83 %. The samples were annealed using the TLD oven type LAB-01/400 and exposed to cobalt-60 source (Gammacell 220 Excel). TL glow curves were recorded using a Harshaw model 3500 TLD reader. The TL glow curve of this material showed a simple, single, peak located at around 150 °C. The most striking dosimetric feature of this nanomaterial was the excellence linearity response of a dose range from 1 Gy up to 100 Gy with R2= 0.9827 compared to the TLD-100 powder with R2= 0.9276. The high linear correlation between dose and TL response to gamma radiation suggest that calcium metaborate nanocrystals can be considered as a promising material to be used in thermoluminescence dosimetry.
Keywords: Calcium borate; Nanocrystals; Thermoluminescence; Solution combustion; Dosimetric